The Effect of Political Skills on Organizational Silence (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: One of the most difficult skills in the contemporary world of organizations in general and human resource departments in particular. Today's organizations suffer from a lot of problems with workers, in addition to many conflicts of all kinds, which causes weakness in the whistle blowing and wasting of many energies and capabilities in it as a result of organizational silence or other variables, which may lead to their failure in many cases, which called for the need Because there is a type of skill different from what it was previously to cope with the changes, the external and internal environment, thus achieving the well-being and mental health of the subordinates, which will reflect its impact on their organizational performance. The main objective of this paper is to consider the concept of political skills and its impact on organizational silence. Design methodology, or approach: These concepts are supported by previous studies, theory, and empirical evidence. Results: Basic staff skills, appropriate training and development, create and improve the nature of existing employees. Where the training will affect the behavior of employees and the development of their basic skills and practical capabilities, which leads to improved performance and more productive changes that work to build employee performance. From the above results, it becomes clear to us that the administration has the ability to persuade and influence others, establish relationships and communicate with others in a positive way. Originality / Value: This paper provides a bridge between political skills and organizational silence. This bridge provides an exciting new way to further study key relationships.